Pemaknaan Pernikahan Pada Tiga Generasi Perempuan Di Desa Rantau Panjang Kecamatan Lingga Utara - Altarizan Altarizan; Nanik Rahmawati; Rahma Syafitri (Lembaga Pengembangan Kinerja Dosen, 2023)
The meaning of marriage in society is important to know. This aims to identify whether or not there is a shift based on generations X, Y and Z in viewing marriage. So that it can reveal the meaning of marriage in society. Marriage is one of the factors why women are strongly encouraged to get married. Marriage is also a way for someone to perfect worship. Each individual also has their own choice in deciding to get married. Therefore, this study aims to describe the meaning of marriage based on generations in Rantau Panjang Village, North Lingga District from several factors of rational choice theory. This research uses a descriptive qualitative approach that aims to conduct in-depth research on the meaning of marriage based on generations. The research method used used Purposive Sampling. Data collection techniques use direct observation and structured interviews to obtain data. The theory used in this research is rational choice by James Coleman. Rational choice theory emphasizes a person to take an action that will utilize resources in achieving a goal. In this study, rational choice theory is used to explain the meaning of marriage in society so that marriage is in accordance with one's personal choice. The results showed that how the meaning of marriage between generations in choosing to get married. Most of them are caused by religious, arranged marriage and financial obligations.